If it's not what You are looking for type in the equation solver your own equation and let us solve it.
r-6=6+7r-4r
We move all terms to the left:
r-6-(6+7r-4r)=0
We add all the numbers together, and all the variables
r-(3r+6)-6=0
We get rid of parentheses
r-3r-6-6=0
We add all the numbers together, and all the variables
-2r-12=0
We move all terms containing r to the left, all other terms to the right
-2r=12
r=12/-2
r=-6
| 2p-4+2p+2=10 | | x*X2+5=-14 | | 6x^2-24x-11=0 | | -4(3x-5)=-13(x-2) | | 348=-4x | | 15j-14j=3 | | 8-2r=38 | | 4a-7+3a+2=30 | | 10x+(3x+22)=360 | | 16c+3c+2c-4c-16c=17 | | 3-(2x-2)=8 | | -8x-25=14 | | 6z+36=3(2z+12) | | c-13=-15 | | 2=8x3=5x4=3x+100 | | 6r+r-6r=7 | | 9(w-6)=3w-42 | | (X)(5x)=180 | | r-6=+7-4r | | 4x+2x+2=2x-7 | | 1.8+2b=6.2 | | (5x)x=180 | | -7=-6÷x | | 5x^2+38x+36=0 | | 4^2x=3.4^x+10 | | -7=x÷-6 | | -7x2+9x+9=-8x2+1 | | 3x+1+146=180 | | (X)(6x+8)(x+12)=180 | | 6t-3=3 | | -4p=-5p-5 | | 7x-55=4x+32 |